IMPOLITENESS STRATEGIES IN NETIZENS COMMENTS ON THE MURDER CASE OF BRIGADIER JOSHUA FOUND ON YOUTUBE: A PRAGMATIC APPROACH - Maresa Manullang; Christina Natalina Saragi; Yessy Octavianna (Sean Institute, 2023)
This study aimed to find out the types of impoliteness strategies based on Jonathan Culpeper theory,1996 and the dominant impoliteness strategies used by the netizen comments about the murder case of Brigadier Joshua found on YouTube Kompas TV. This study was conducted by applying the descriptive qualitative method. The source of the data was taken from the comment column posted by netizens about the murder case of Brigadier Joshua. The technique for analyzing the data is qualitative research. This research showed that four impoliteness are used: Bald on Record impoliteness, Positive Impoliteness, Negative Impoliteness, and Sarcasm/Mock Politeness. There were 400 comments. In total, there are 70 comments on Bald on Record (17,5%), 100 comments on Sarcasm/Mock Politeness (25%), 60 comments on Positive Impoliteness (15%), and 170 comments on Negative Impoliteness (42,5%). Based on the comments that have been analyzed, the researcher concluded that the dominant Impoliteness strategy that is used by netizens is Negative Impoliteness. Netizens mostly used Negative impoliteness to express their negative attitude on giving online comments about the murder case of Brigadier Joshua found on YouTube. The reason could be, that in comparison to other strategies, these have many sub-strategies that support positive and negative impoliteness strategies, such as ignore, uncaring, seek disagreement, scorning, ridiculing the other, frightening, make the other comfortable, call the other name, use taboo words, fearing the others and so on.